An overview of post-extraction secondary forests in Indonesia - Kartawinata, K.; Riswan, S.; Gintings, A.N.; Puspitojati, T. (2001)
Indonesia has extensive areas of post extraction secondary forests and degraded lands arising from intensive exploitation of forest resources in recent decades. Using the area of forests resulting from selective logging practices as an estimate, in year 2000, post extraction secondary forests covered about 23 million ha, or about 55% of the total concession area. This paper analyses the underlying causes of transformation of primary to secondary forests and degraded lands, including policy and regulations in forestry and forest resources, poor enforcement of regulations, and the lack of recognition of timber exploitation rights for local communities. The government is committed to promoting participation of local communities in managing forests. Recent policy changes for ameliorating some of the degrading factors have resulted in increased pressure on secondary forests due to rampant illegal logging and use claims by local communities and land speculators. While the largest proportion of post extraction secondary forests has been maintained as part of the permanent forest estate, substantial areas have been converted for swidden agriculture, industrial tree and estate crop plantations and transmigration areas. Local community involvement and an understanding of the underlying degradation pressures would be imperative for the effective rehabilitation and sustainable management of post extraction secondary forests.